Kinerja Kepala Sekolah dalam Mengimplementasikan Manajemen Berbasis Sekolah di SMP Negeri 2 Samarinda - Nikolaus Anggal (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2018)
This study aims to determine the performance of school principals in implementing school-based management and how the characteristics of school-based management are applied in the State Preventing School 2 Samarinda. The approach is qualitative with descriptive methods. Data collection was done using observation, interview and documentation study techniques. The subjects of this study were the principal, vice principal, teacher, and students. Data analysis techniques are carried out by organizing and sorting data in patterns, categories, and one basic description to formulate the research hypothesis. The results showed that the performance of the principal in implementing School Based Management was open and involved educators and education personnel in planning and implementing School Based Management. The characteristics of School Based Management are processing the resources of educators and education to improve the quality of schools, processing a compact and transparent team work from all staff in the school. In addition, principals are always looking for solutions to every problem in implementing School Based Management.